Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7. Issue 5 (4th March 2017) - He, Wei-Jun; Zhou, Xiao-Jiang; Qin, Xiao-Chu; Mai, Yong-Xin; Lin, Xiu-Ping; Liao, Sheng-Rong; Yang, Bin; Zhang, Tianyu; Tu, Zheng-Chao; Wang, Jun-Feng; Liu, Yonghong
Abstract: Fifteen compounds, including six quinone/hydroquinone meroterpenoids, purpurogemutantin (1 ), macrophorin A (2 ), 4′-oxomacrophorin (3 ), 7-deacetoxyyanuthone A (4 ), 2, 3-hydro-deacetoxyyanuthone A (5 ), 22-deacetylyanuthone A (6 ), anicequol (7 ), three roquefortine derivatives, roquefortine C (8 ), (16 S )-hydroxyroquefortine C (9 ), (16 R )-hydroxyroquefortine C (10 ), dihydroresorcylide (11 ), nectriapyrone (12 ), together with three fatty acid derivatives, methyl linoleate (13 ), phospholipase A2 (14 ), methyl elaidate (15 ), were isolated from the sponge-derived fungus Gliomastix sp. ZSDS1-F7 isolated from the sponge Phakellia fusca Thiele collected in the Yongxing island of Xisha. Their structures were elucidated mainly by extensive NMR spectroscopic and mass spectrometric analyses. Among these compounds, compounds1 –3 and5 –7 showed significant in vitro cytotoxicities against the K562, MCF-7, Hela, DU145, U937, H1975, SGC-7901, A549, MOLT-4 and HL60 cell lines, with IC50 values ranging from 0.19 to 35.4 μM. And compounds2 –4 exhibited antitubercular activity with IC50 values of 22.1, 2.44 and 17.5 μM, respectively. Furthermore, compound7 had anti-enterovirus 71 activity with MIC value of 17.8 μM. To the best of our knowledge, this is the first report to product two quinone/hydroquinone meroterpenoids skeletons (linear skeleton and drimane skeleton) from the same fungal strain. Abstract :